Think about historiographical construction from its operational complexity. Interview whit Fernando Betancourt Martínez (Palimpsesto, 2017)
Pensar la construcción historiográfica desde su complejidad operativa: entrevista al historiador Fernando Betancourt Martínez
Keywords: Interview; Historiography; Fernando Bentacourt.